Impact of paternal alcohol consumption on fetus and adolescence - Farooqui, Sabeeh Khawar; Mehak Barolia (Journal of the Pakistan Medical Association, 2022)
Madam, Ethanol being a carcinogen as well as a teratogen agent can be injurious to the consumer but also can induce cognitional impairments in the progeny. However, chronic consumption significantly impacts liver and cardiovascular system leading to alcoholic liver or heart diseases. The alcohol consumption per capita of males in Pakistan is known to be significantly higher than that of women (1). Paternal alcohol consumption has harmful and adverse effects on developing fetus (3), leading to behavioral and intellectual problems within the adolescent age group. Despite its delirious effect, alcohol consumption has increased in Pakistan over the years. The total increase in alcohol consumption per capita (15+) age group has a value of 0.084 from the interval 2000-2018 which is quite significant when compared to Bangladesh which shows a drastic drop to a value of 0.056 in its alcohol consumption per capita in the same time interval (3). As of yet, there is no proper awareness regarding the harmful effects of paternal alcohol consumption in this high risk age group. A study in 2015 suggested that paternal ethanol induces physiologic abnormalities in offspring in the absence of maternal ethanol exposure (2). A prior study published in 1984 also concluded that paternal alcohol usage affects cognitive behavior and decreases the performance of their child (age 16+) with regards to his intelligence (4). Cognitive battery test, showed that sons of alcoholic fathers have a delayed first response time compared with non-alcoholic fathers (p<0.01). According to statistical data by The World Bank in 2018, it was recorded that alcohol consumption rate is 0.57 per capita in males aged (15+) in Pakistan (3), This triggers an alarming situation that the next few generations in Pakistan may face severe consequences of foetal disorders leading to cognitive disabilities in children (age 16+). Physicians should ensure to counsel the couple regarding the adverse effects of alcohol on childbirth and its after-effects in the adolescent age. If planning to conceive, the couple should be mindful of reducing the consumption of alcohol. Moreover, the couple should discuss this matter with the physician if they are chronic alcohol consumers so that they are aware of the consequences of alcohol consumption beforehand. Continuous...